Advances in research of the artificial cultivation of Ophiocordyceps sinensis in China. (September 2014) - Zhou, Xuan-Wei; Li, Lin-Jun; Tian, En-Wei
Abstract Ophiocordyceps sinensis (syn. Cordyceps sinensis), a traditional Chinese medicine called DongChongXiaCao (DCXC) in Chinese, is well known and has been used in Asia countries since the fifteenth century, and it contains some valuable medicinal component defined by modern pharmacological science. DCXC only appears at high altitudes on the Qinghai-Tibetan Plateau. Consequently, it is difficult to find and harvest. Because of its rarity and medicinal value, DCXC has always been one of the most expensive medicines known. As the price of DCXC has risen in recent years, thousands of migrants have entered into the various grasslands to search for them in season, which makes ecological environments of the grassland more fragile. In order to relieve the environmental pressures and protect this valuable resource, the artificial cultivation of DCXC involving two aspects of the genus Hepialus and the fungi of the host larvae should be employed and applied at the first available time point. In this article, the reproduction of moth larvae of the genus Hepialus is first described, which includes their ecological characteristics and the methods of artificial feeding. Second, the generation and isolation method of the fungi from DCXC are subsequently summarized, and then the mechanism of fungal spores to attack the moth larvae are restated. Finally, the basic model of artificial cultivation of DCXC is introduced; meanwhile, the potential application of modern biotechnology to the artificial cultivation is analyzed in prospect. This review article will not only expand people's knowledge regarding the artificial cultivation of DCXC, but also hopefully provide an informative reference for the development of this valuable resource and the environmental protection of alpine meadows.